A study on Malaysian roadside safety adopting safety recovery zone corridor concept - Ahmad Kamal, Kunji (2019)
Run-off-road vehicle collisions with roadside obstructions such as trees, utility poles, concrete drains and culverts, roadside slopes and signboard pillar and roadside barriers known as hazards have contributed to a large proportion of fatalities and severe injuries to the vehicle occupants. The unforgiving design of roadside geometry had multiplied the issue when the skidding vehicles were unable to traverse to safety. The mistakes unfriendly design policy has been causing fatal accidents and severe injuries because it forms the basis for engineering design and construction works. Introducing the concept of safety recovery zone corridor will ensure the roadside is free of obstructions or hazards, an environment forgiving to skidding errant vehicles. This missing chapter has inspired this research work by carrying out live field experiments to determine the widths of roadside safety recovery zone corridors for the various vehicle travelling speeds and roadside gradients for the use of engineers in the road and highway design. The research discovered that the current Malaysian landscape design guide permits the planting of trees classified as hazard within the safety recovery zone corridor, a clause conflicting to the forgiving design concept, and has been identified for adjustment. A case study was carried out to Malaysian roadside hazards to reveal the depth of the existing construction problems, demonstrated some examples of practical design improvement. The research process included live field experiments in determining the relationship between widths of roadside safety recovery zone corridor against the various roadside slopes for a set of vehicles design speeds specified in the Malaysian design guide. The study selected ten driving test fields from four states, namely Pahang, Johor, Selangor, and Perak of Malaysia, with a variety of roadside slope gradients and ground surface conditions. The sampling of 4 states represents 30% of 13 states of Malaysia. Four fit and fully licensed drivers aged between 20 to 24 years safely executed the field driving tests. The selected four cars for field testing works ranging from 1.3 to 2.3 litres cylinder capacities were namely Saga FLX 1.3, Honda City 1.5, Mazda3 2.0 and Ford Escape XLS 2.3. All the cars were less than ten years old and in good working condition. The tests were carried out by driving the vehicle at the desired speed, and then skidding off the travel lane through the marked red line of vehicle's exit angles painted on the road, and then traversing back to the travel lane. The driving test was repeated five times for each selected travelling speed, as further repetition may damage the ground surface and impair experiment's result. The study showed that the widths of safety recovery zone corridor measured perpendicular from travel lane increase with the increase of the roadside slope gradients and the vehicle travelling speeds. Depending on the road design types and roadside gradients, the discovered minimum width of safety recovery zone corridor for rural roads is ranging between 1.64 to 8.07 meters for vehicle speeds between 50 km/h to 110 km/h. On the other hand, the discovered minimum width of safety recovery zone corridor for the urban roads is ranging between 1.64 to 6.82 meters for vehicle speeds between 50 km/h to 100 km/h. The outcome of this study proved the necessity to fill the gap in the design chapter with safety recovery zone corridor concept in Malaysian standard to reduce road traffic fatalities and severe injuries.